HUBUNGAN SELF-CONTROL DENGAN ONLINE GAMING ADDICTION PADA MAHASISWA - Elvina Ananta Sutedjo Sanjoto; Puspita Puji Rahayu (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
Emotional pressure due to the high burden of academic assignment evaluations and the use of cyber media as an escape from daily stressors underlie this research. These operational issues trigger self-regulation failures, negatively impacting sleep patterns, social interaction functions, and decreased student academic performance. The main focus of this scientific study is to dissect and empirically test the relationship between self-control and the tendency towards online gaming addiction in active college students. The steps of this quantitative, descriptive, correlational research pathway were operated using an online questionnaire, reaching 117 respondents through a purposive sampling technique. Primary data measurement adopted the Brief Self-Control Scale (BSCS) and the Indonesian version of the Internet Gaming Disorder Scale (IGDS), which were then statistically executed through a Pearson correlation test using the SPSS 26 computer program. The quantitative data empirically revealed a significant negative relationship with a correlation coefficient of minus 0.329 at a significance parameter of p 0.000. This finding confirms that the higher a student's self-control capacity, the lower their level of compulsive dependence on virtual games. The main conclusion is that strengthening executive control functions and delaying gratification have been shown to moderately inhibit digital addiction. Academic institutions are recommended to draft educational programs for regulating adaptive behavior. ABSTRAK Tekanan emosional akibat tingginya beban evaluasi tugas akademik serta pemanfaatan media siber sebagai pelarian dari stres harian melatarbelakangi kegiatan penelitian ini. Masalah operasional tersebut memicu kegagalan regulasi diri sehingga berdampak buruk pada pola tidur, fungsi interaksi sosial, serta penurunan performa studi mahasiswa. Fokus utama kajian ilmiah ini adalah membedah dan menguji secara empiris hubungan antara self-control atau kontrol diri dengan kecenderungan online gaming addiction pada mahasiswa aktif. Langkah-langkah jalur riset kuantitatif deskriptif korelasional ini dioperasikan menggunakan kuesioner daring dengan menjangkau 117 responden melalui teknik penarikan sampel purposive sampling. Pengukuran data primer mengadopsi instrumen Brief Self-Control Scale (BSCS) dan Internet Gaming Disorder Scale (IGDS) versi Bahasa Indonesia, yang selanjutnya dieksekusi statistik lewat uji korelasi Pearson menggunakan program komputer SPSS 26. Data kuantitatif secara empiris menyingkap adanya hubungan negatif yang signifikan dengan capaian koefisien korelasi sebesar minus 0,329 pada parameter signifikansi p senilai 0,000. Temuan ini menegaskan bahwa semakin tinggi kapasitas pengendalian diri mahasiswa, maka semakin rendah tingkat ketergantungan kompulsifnya terhadap permainan virtual. Simpulan utama membuktikan bahwa penguatan fungsi kontrol eksekutif dan penundaan kepuasan (delay of gratification) terbukti moderat menghambat adiksi digital. Institusi akademik direkomendasikan menyusun draf edukasi regulasi perilaku adaptif.